Market Exit Through Divestment—The Effect of Accounting Bias on Competition - Chen, Hui; Jorgensen, Bjorn N. (Management Science, 2018)
We analyze the effect of accounting bias on the competition and market structure of an industry. In our model, firms’ interim accounting reports on investment projects may contain bias introduced by the mandatory accounting system. We find that this bias strictly decreases firms’ profits when investors do not have an abandonment option, but different results emerge when we allow the investors to divest in the interim. Specifically, a conservative accounting regime may increase the likelihood of projects being discontinued, inducing some firms to exit from the product market and leaving rivals to capture their market share. A conservative regime can thus soften market competition and result in ex ante higher investment payoff, higher consumer surplus, and higher total social welfare. Since industries often have common reporting standards, we also identify the degrees of industry-wide accounting bias that maximize the expected investor payoffs. Finally, we allow for investors to coordinate their divestment decisions when both firms report unfavorable costs and show an improvement to both firm profits and consumer surplus. This paper was accepted by Mary Barth, accounting.